2024
DOI: 10.1590/1983-21252024v3711728rc
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and potassium interaction in oxisol soils under BRS 394 wheat cultivation

Juliana T. S. Paludo,
Edna M. Bonfim-Silva,
Tonny J. A. da Silva
et al.

Abstract: Potassium and nitrogen are essential nutrients and their uptake and distribution within plants must be coordinated for optimum growth and development. We evaluated the interaction between nitrogen and potassium fertilization on the development of BRS 394 wheat, and the nitrate and ammonium levels in Oxisol soils. A 52 factorial design was used in a greenhouse experiment, with four replicates in randomized blocks, corresponding to five doses of nitrogen (0, 70, 140, 210, and 280 mg dm-3) and five doses of potas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have shown that when the activity of soil alkaline phosphatase is enhanced, the rate of conversion of organic phosphorus to inorganic phosphorus in the soil accelerates, increasing the content of available phosphorus ( Kuzmanović et al., 2024 ; Rocabruna et al., 2024 ). An increase in the activity of soil nitrate reductase can affect the rate of soil denitrification and the amount of nitrogen available to plants ( Li et al., 2024 ; Paludo et al., 2024 ). Soil urease catalyzes the hydrolysis of urea into NH 3 , which is further converted to NH 4+ through proton exchange ( Qin et al., 2010 ; Pinto et al., 2014 ; Chen et al., 2021 ; Duff et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that when the activity of soil alkaline phosphatase is enhanced, the rate of conversion of organic phosphorus to inorganic phosphorus in the soil accelerates, increasing the content of available phosphorus ( Kuzmanović et al., 2024 ; Rocabruna et al., 2024 ). An increase in the activity of soil nitrate reductase can affect the rate of soil denitrification and the amount of nitrogen available to plants ( Li et al., 2024 ; Paludo et al., 2024 ). Soil urease catalyzes the hydrolysis of urea into NH 3 , which is further converted to NH 4+ through proton exchange ( Qin et al., 2010 ; Pinto et al., 2014 ; Chen et al., 2021 ; Duff et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%